SHORT NOTE Growth, forage and grain yields of barley as affected by irrigation regime and method of sowing in Sudan Gezira - Mohamed, Mahasin A.; A. M. Khair, Mohammed (Gezira Journal of Agricultural Science; Vol 14 No 1 (2016), 2016)
Barley ( Hordium vulgare ) is an important multipurpose crop used as feed for animals, malt and human food. Its importance lies in its ability to grow and produce in marginal environments, which are often characterized by drought, low temperature and salinity, (Maas and Hoffiman, 1997 and Baum et al .,2004). Barley is most commonly grown for cereal silage and can produce good yields of high quality feed if water is available. Compared to alfalfa, it grows during a short period and its water requirements are less. The full season water requirements of alfalfa are 900mm of water, one crop of barley silage may only require about 375mm of water for a 7.5 to 10 ton/ha yield. The three years average amount of the applied water for barley on 10 days interval was only 4525 m 3 /ha, compared to other field crops, the average applied irrigation water for barley is low and water productivity is high even if irrigated every 10 days (Mahasin and Khair, 2014). Hand broadcasting is commonly used to sow wheat (84%) and barley (92%) while covering with mold-board is used to a lesser extent with wheat (48%) than with barley (68%).